Environmental, Social, Governance (ESG), And Financial Performance of European Banks - Oana Marina Bătae; Voicu-Dan Dragomir; Liliana Feleagă (Journal of Accounting and Management Information Systems (JAMIS), 2020)
Research Question: How do ESG and financial performance indicators vary according to different classifications of European banks? Motivation - Banks' ESG performance and its relationship with corporate financial performance represents a field of continuous interest for researchers and practitioners. The results of previous studies are still mixed, either positive, negative, or even neutral. What's new? The novelty of this paper is represented by the statistical comparison of variables that measure the ESG and financial performance of European banks based on three classifications that we propose (i.e. the geographical regions of Europe, functional currency, and cluster analysis on GDP and population of European countries, respectively). To the best of our knowledge, there are no studies applied to the banking sector, analyzing the selected variables between groups of banks according to the aforementioned classifications. So what? We contribute to the field by extending Thomson Reuters' grouping of banks (Emerging and Developed Europe) with three more classifications. The comparison of ESG and financial performance data contributes to practice by highlighting which parts of Europe contain the banks with the highest and respectively the lowest values of ESG and financial performance, controversies, and audit fees. Therefore, the results will help investors, policymakers, regulatory bodies, bank managers, and auditors to acknowledge the significant differences within Europe and adopt appropriate measures that could improve the financial and sustainability performance of banks. Data - We collect data from Thomson Reuters Eikon, World Bank statistics, and EuroVoc for 108 European banks (81 from Developed Europe and 27 for Emerging Europe) for 2018, the most recent year on which all information is available. Tools - We conduct a cluster analysis on the macroeconomic variables of the study: the GDP per capita and the population. We used group tests and the ANOVA test as methods in analyzing the results. Findings and Contribution - We contribute with a quantitative study that fills the gap in the literature regarding significant differences that are obtained in ESG and financial performance of banks classified as Developed Europe versus Emerging Europe; Eurozone versus non-Euro countries; Western, CEE, Northern, and Southern banks; small GDP – large population and large GDP – small population clusters. Our methodology will improve future research in adopting better and more transparent classifications of companies analyzed at an international level.
Keywords: F64; G21; G34; M14; O16; 650; Banking sector; ESG performance; Corporate social responsibility; Environmental performance; Corporate governance; Emerging Europe; Developed Europe